Expression of truncated human epidermal growth factor receptor 2 on circulating tumor cells of breast cancer patients. Issue 1 (December 2015) - Kallergi, Galatea; Agelaki, Sofia; Papadaki, Maria; Nasias, Dimitris; Matikas, Alexios; Mavroudis, Dimitris; Georgoulias, Vassilis
Abstract Introduction The truncated form of human epidermal growth factor receptor 2 (p95HER2) lacks the HER2 extracellular domain and has been associated with poor prognosis and resistance to trastuzumab. In the present study, the expression of p95HER2 was investigated on circulating tumor cells (CTCs) from breast cancer patients. Methods Triple-staining immunofluorescent experiments were performed on peripheral blood mononuclear cells' (PBMCs) cytospins obtained from patients with early (n = 24) and metastatic (n = 37) breast cancer. Cells were stained with the pancytokeratin (A45-B/B3) antibody coupled with antibodies against the extracellular (ECD) and the intracellular (ICD) domains of HER2. Slides were analyzed with either confocal laser scanning microscopy or with the Ariol system. Results HER2-positive CTCs were identified in 55.6 % of early and 65.2 % of metastatic CTC-positive breast cancer patients. p95HER2-positive CTCs were identified in 11.1 % of early and 39.1 % of metastatic breast cancer patients (p = 0.047). In 14 patients with metastatic HER2-positive breast cancer, CTCs were also analyzed before and after first-line trastuzumab therapy. Trastuzumab reduced the percentage of patients with full-length HER2-positive CTCs from 70 % at baseline to 50 % (p = 0.035) after treatment while increased the percentage of patients with p95HER2-positive CTCs from 40 % to 63 %. Moreover, the overall survival of metastatic patients with p95HER2-positive CTCs was significantly decreased (p = 0.03). Conclusions p95HER2-positive CTCs can be detected in both early and metastatic breast cancer patients. Their incidence is increased in the metastatic setting and their presence is associated with poor survival. Longitudinal studies during anti-HER2 treatment are required to determine the clinical relevance of p95HER2-expressing CTCs.